Decompensated cirrhosis and liver transplantation negatively impact in DAA treatment response: Real‐world experience from HCV‐LALREAN cohort. Issue 12 (13th August 2020) - Ridruejo, Ezequiel; Piñero, Federico; Mendizabal, Manuel; Cheinquer, Hugo; Wolff, Fernando Herz; Anders, Margarita; Reggiardo, Virginia; Ameigeiras, Beatriz; Palazzo, Ana; Alonso, Cristina; Schinoni, María Isabel; Zuain, María Grazia Videla; et al.
Abstract: Introduction: Although the effectiveness of direct‐acting antivirals (DAAs) for the treatment of chronic hepatitis C virus (HCV) has been reported in real‐world settings, predictive factors of treatment failure are lacking. Therefore, we sought to explore the baseline predictors of treatment response to DAAs. Methods: This was a prospective multicenter cohort study from the Latin American Liver Research Educational and Awareness Network (LALREAN) including patients who received DAA treatment from May 2016 to April 2019. A multivariate logistic regression model was conducted to identify variables associated with unachieved sustained virological response (SVR), defined as treatment failure (odds ratios [OR] and 95% confidence intervals [CIs]). Results: From 2167 patients (55.2% with cirrhosis) who initiated DAA therapy, 89.4% completed a full‐course treatment (n = 1938). Median treatment duration was 12 weeks, and 50% received ribavirin. Definitive suspension due to intolerance or other causes was observed in only 1.0% cases (n = 20). Overall non‐SVR12 was 4.5% (95% CI, 3.5‐5.7). There were no significant differences in treatment failure according to HCV genotypes and the degree of fibrosis. Independently associated variables with DAA failure were liver function impairment according to the Child‐Pugh score B OR, 2.09 ( P = .06), Child‐Pugh C OR, 11.7 ( P < .0001); and liver transplant (LT) recipient OR, 3.75 ( P = .01). Conclusion: In this real‐life setting, higher DAA treatment failure rates were observed in patients with decompensated cirrhosis and in LT recipients. These predictive baseline factors should be addressed to individualize the appropriate time‐point of DAA treatment (NCT03775798; www.clinicaltrials.gov ). Highlights: SVR12 failure in clinical practice is low in Latin America (4.5%). End stage liver disease (Child B/C scores) and liver transplantation were independent predictors of DAA failure. Early DAA treatment to prevent disease progression is needed to avoid nonresponse to treatment.